Запорозький Ґард: правда й вигадки - Товкайло, М.Т.; Титова, О.М. (Археологія, 2016)
Майже два десятиліття триває боротьба громадськості та пам’яткоохоронних органів за збереження низки пам’яток, які в сукупності визначають історико-культурну цінність пам’ятки культурної спадщини «Історичний ландшафт центру Буго-Ґардівської паланки Війська Запорозького». У статті розглянуто перипетії цієї боротьби, маніпуляції і фальсифікації навколо питання місцезнаходження Ґардового острова, похідної церкви Покрови Пресвятої Богородиці, Паланки та ін. For almost two decades, the fight of public and monuments protection authorities for the preservation of «Historic landscape of the center of the Zaporizhia Army’s Buh-Gard Palanka», a cultural heritage monument of national importance (security number 140001-H), located on the land plots, one of the users of which is the state enterprise National Nuclear Energy Generating Company «Energoatom». This article discusses the vicissitudes of this struggle, the manipulations and falsifications relating the location of historic Gardiv Island, the Protection of Ever-Virgin Mary Campaign Church, Palanka, and other monuments of the period from the 16th to the 18th centuries related to the history of the Zaporizhia Sich. Analyzed are available on this issue historic, archaeological, ethnographic, cartographic, toponymic, and other sources, a critical analysis of which allows to make an unambiguous conclusion: historic Gardiv Island at the end of one of the largest on the Southern Buh River Gardiv threshold is situated in the tract with the same name of Gard, namely, 2,0 km to southeast of Bohdanivka Village in Domanivka District of Mykolayiv Oblast. Currently, it is called Klepanyi Island. Despite the fact that it is flooded during spring high water, it is here where the Cossacks’ and fishermen’s dwellings were situated and where an energetic economic activity was conducted, due to the largest fisheries in the Zaporizhia Sich, Old or Cossacks’ Gard, located at the north of the island. It is also here, where the Protection of Ever-Virgin Mary Campaign Church was situated on one of the highest stones. Почти два десятилетия продолжается борьба общественности и органов охраны памятников за сохранение памятника культурного наследия национального значения «Исторический ландшафт центра Буго-Гардовской паланки Войска Запорожского» (охранный № 140001-Н), расположенного на землях, одним из пользователей которых является государственное предприятие Национальная атомная энергогенерирующая кампания «Энергоатом». В статье рассматриваются перипетии этой борьбы, манипуляции и фальсификации, касающиеся местонахождения исторического Гардового острова, походной церкви Покровы Пресвятой Богородицы, Паланки и других памятников ХVI—ХVIII вв., связанных с историей Запорожской Сечи. Рассматриваются имеющиеся по этой проблеме исторические, археологические, этнографические, картографические, топонимические и другие источники. Их критический анализ позволяет сделать однозначный вывод: исторический Гардовый остров, которым заканчивается один з самых больших на Южном Буге Гардовый порог, находится в одноименном урочище Гард, в 2,0 км к юго-востоку от с. Богдановка Доманевского р-на Николаевской обл. В настоящее время он носит название Клепанный остров. Несмотря на то, что он подтапливался во время весенних половодий, именно здесь были жилища казаков и рыболовов, здесь велась активная хозяйственная деятельность, связанная с расположенным в северном конце острова самым большим в Запорожской Сечи рыбным промыслом — Старым или Казацким гардом. Здесь же, на одном из самых высоких камней, стояла у запорожцев походная церковь Покровы Пресвятой Богородицы.